Diagnosis of Human Echinococcosis via Exhaled Breath Analysis: A Promise for Rapid Diagnosis of Infectious Diseases Caused by Helminths. (16th July 2018) - Welearegay, Tesfalem Geremariam; Diouani, Mohamed Fethi; Österlund, Lars; Borys, Sebastian; Khaled, Samira; Smadhi, Hanen; Ionescu, Florina; Bouchekoua, Meriam; Aloui, Dorsaf; Laouini, Dhafer; Cindemir, Umut; Ionescu, Radu
Abstract : In this study we identified putative breath biomarkers for the 2 main types of human echinococcosis disease (cystic and alveolar), and we demonstrated a noninvasive, fast, easy-to-operate, and nonexpensive sensing test for human echinococcosis diagnosis through exhaled breath analysis. Abstract: Background: Human echinococcosis is a neglected infectious disease affecting more than 1 million people globally. Its diagnosis is expensive and difficult because of lack of adequate resources in low-resource locations, where most cases occur. Methods: A group of volunteers diagnosed with the 2 main types of echinococcosis and corresponding control groups were recruited from hospitals in Tunisia (32 patients with cystic echinococcosis and 43 controls) and Poland (16 patients with alveolar echinococcosis and 8 controls). Breath samples were collected from all patients and analyzed by gas chromatography coupled to mass spectrometry, and a specifically developed electronic nose system. Results: The chemical analysis revealed statistically different concentrations of 2 compounds in the breath of patients with cystic echinococcosis compared to controls, and statistically different concentrations of 7 compounds in the breath of patients with alveolar echinococcosis compared to controls. The discrimination accuracy achieved by the electronic nose system was 100% for cystic echinococcosis and 92.9% for alveolar echinococcosis, while the discrimination accuracy between these 2 patient groups was 92.1%. Conclusion: Here we advocate a noninvasive, fast, easy-to-operate and nonexpensive diagnostic tool for the diagnosis of human echinococcosis disease through exhaled breath analysis, suitable for early diagnosis and population screening.